Cochlear implant: post-surgical complications - Moreira Souza, Alex; Daniel Gomes , Davi; Alexandre Malheiros Sales , Marcos; Lorena Batista da Silva, Raiza; Júlia Markiv, Ana; Clara Cachoeira, Anna; de Liz Gonzaga dos Santos, Camila; Wasum dos Santos, Eduardo; Grando, Gabriela; Vendruscolo Devenci, Guilherme; Raquel Tremea, Julia; Luiza Beck, Maria; et al. (Brazilian Journal of Implantology and Health Sciences, 2025)
The aim of this study was to develop an article on complications associated with Cochlear Implant (CI) surgeries performed over a decade at the University Hospital (HU) – Federal University of Santa Catarina (UFSC). A recurrence rate of approximately 9% of complications was observed. Of these, vertigo, device displacement, surgical infection and facial paralysis were the most common.